READINESS FOR CHANGE RESEARCH IN MANAGEMENT: A SCOPUS-BASED BIBLIOMETRIC REVIEW AND THEMATIC SYNTHESIS (2021–2026) - Rosalina Hutahaean (Journal of Social and Economics Research, 2026)
Readiness for change has become a central construct in management and human resource management (HRM) scholarship because organizational change outcomes depend not only on formal change design but also on the psychological and structural preparedness of organizational members. Despite its relevance, the literature remains fragmented across levels of analysis, adjacent constructs such as resistance, buy-in, and engagement, and diverse organizational contexts including public organizations, healthcare, regulated industries, and digital transformation. This study conducts a Scopus-based bibliometric review and thematic synthesis of readiness-for-change research in management and HRM-oriented literature published between 2021 and 2026. Bibliographic data were retrieved from Scopus on 3 May 2026 using a TITLE-ABS-KEY search strategy and refined to final-stage, open-access journal articles in Business, Management and Accounting, resulting in a final corpus of 52 articles. The analysis combines descriptive bibliometric mapping, VOSviewer keyword co-occurrence analysis, and country-level bibliographic coupling. The results show an uneven publication trajectory, with the literature concentrated among a limited group of authors, affiliations, and countries. The co-word structure positions change management and organizational change as central hubs linking six mechanism-oriented themes: communication and sensemaking, leadership and trust, culture and change capability, intervention design and implementation gaps, technology-enabled change contexts, and employee well-being risks. Building on these findings, the study proposes an HRM-grounded conceptual model connecting readiness-building mechanisms to proximal and distal change outcomes under explicit boundary conditions. The review contributes by clarifying the multi-level nature of readiness for change, translating science-mapping outputs into theory-building mechanisms, and outlining a future research agenda for cross-level, longitudinal, and context-sensitive readiness research